Syncope and COVID-19 disease - A systematic review - Maria Raquel Reis Falcão de Freitas (2022)
Background Syncope is not a common manifestation of COVID-19, but it may occur in this context and it can be the presenting symptom in some cases. Different mechanisms may explain the pathophysiology behind COVID-19 related syncope. In this report, we aimed to examine the current frequency and etiology of syncope in COVID-19. Methods A systematic review across PubMed, ISI Web of Knowledge and SCOPUS was performed, according to PRISMA guidelines, in order to identify all relevant articles regarding both COVID-19 and syncope. Results We identified 136 publications, of which 99 were excluded. The frequency of syncope and pre-syncope across the selected studies was 4.2% (604/14,437). Unexplained syncope was the most common type (87.9% of the episodes), followed by reflex syncope (7.8% of the cases). Orthostatic hypotension was responsible for 2.2% of the cases and syncope of presumable cardiac cause also accounted for 2.2% of cases. Arterial hypertension was present in 52.0% of syncope patients. The use of angiotensin receptor blockers or angiotensin converting enzyme inhibitors were not associated with an increased incidence of syncope (chi-square test 1.07, p 0.30), unlike the use of beta-blockers (chi-square test 12.48, p < 0.01). Conclusion Syncope, although not considered a typical symptom of COVID-19, can be associated with it, particularly in early stages. Different causes of syncope were seen in this context. A reevaluation of blood pressure in patients with COVID-19 is suggested, including reassessment of antihypertensive therapy, especially in the case of beta-blockers.